Pulmonary immunization with a recombinant influenza A virus vaccine induces lung-resident CD4+ memory T cells that are associated with protection against tuberculosis. Issue 6 (November 2018) - Flórido, Manuela; Muflihah, Heni; Lin, Leon; Xia, Yingju; Sierro, Frederic; Palendira, Mainthan; Feng, Carl; Bertolino, Patrick; Stambas, John; Triccas, James; Britton, Warwick.
Abstract The lung is the primary site of infection with the major human pathogen, Mycobacterium tuberculosis . Effective vaccines againstM. tuberculosis must stimulate memory T cells to provide early protection in the lung. Recently, tissue-resident memory T cells (TRM ) were found to be phenotypically and transcriptional distinct from circulating memory T cells. Here, we identifiedM. tuberculosis- specific CD4+ T cells induced by recombinant influenza A viruses (rIAV) vaccines expressingM. tuberculosis peptides that persisted in the lung parenchyma with the phenotypic and transcriptional characteristics of TRMs . To determine if these rIAV-induced CD4+ TRM were protective independent of circulating memory T cells, mice previously immunized with the rIAV vaccine were treated with the sphingosine-1-phosphate receptor modulator, FTY720, prior to and during the first 17 days ofM. tuberculosis challenge. This markedly reduced circulating T cells, but had no effect on the frequency ofM. tuberculosis- specific CD4+ TRMs in the lung parenchyma or their cytokine response to infection. Importantly, mice immunized with the rIAV vaccine were protected againstM. tuberculosis infection even when circulating T cells were profoundly depleted by the treatment. Therefore, pulmonary immunization with the rIAV vaccine stimulates lung-resident CD4+ memory T cells that are associated with early protection against tuberculosis infection.